Residents’ needs and organisers’ goals towards the organisation of Monsoon Cup Event, Malaysia - Abdullah, Nawal Hanim; Patterson, Ian; Pegg, Shane; Awang, Khairil Wahidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
The Monsoon Cup sporting event is an international yachting regatta held annually in Pulau Duyong, Terengganu, Malaysia during monsoon season between November and January. This research is significant for stakeholders (the community and organisers) in terms of promoting a more transparent process for managing and organising of the Monsoon Cup sailing event. The aim of this research is to examine the social and economic needs of the residents and the goals of the organisers’ (government and Event Company) in organising the Monsoon Cup event. This research used qualitative technique and data were collected through in-depth semi-structured interview with 14 individuals from the organizing team and 36 local residents from Pulau Duyong. The collected data was analysed using thematic content analysis. This research used social exchange theory to develop its theoretical framework. Several important themes emerged from the interviews with the residents that the event would provide positive economic impact especially in increasing income and providing new business opportunities. The interviews with the organisers revealed some important goals which were to promote Terengganu internationally, to provide source of income, to promote traditional boat making industry and to encourage the sport of sailing. Finally, this research had exposed the similarities and differences between residents’ needs and organisers’ goals which can provide strategies to achieve mutual understanding between the key stakeholders.